Completely free, however : an Analysis of Free-to-Play Video Games and Their Attention and Impatience Economic Practices and Expressions of Freeness on Their Google Play sites - Puolakka, Lassi (fi=Turun yliopisto|en=University of Turku|, 2017)
This MA thesis studies how freenessis expressed on the Google Play sites of ten free-to-play gamesandwhether the games are as free as advertised. The gameswere ten top grossing gameson the Google Play store on 10thof March 2016. Freemium services offer a rudimentary service or application for free but charge for a more comprehensive version. Free-to-play games, i.e. freemium games, areavailable for free but monetise via in-app-purchases of in-game goods, content or features. As these games most often have non-free goods, features and content, calling them free is not straightforward –yet the games often are marketed as such. This could lead to misunderstandings as players might expect the games to be free as advertised but find out upon playingthat it is not entirely so. This thesis studies whether top-grossing free-to-play games are advertised as free, whether they are free, and how misunderstandings can arise if they are not as free as advertised. The method of this study uses four theories, involves playing the games to get a picture of their possible restrictionsas well as compiling a synthesis of dictionary entries of 'free' to base the notion of freeness on. First the games are played to get an understanding of their extent of freeness. The restrictions of the games are considered with the ideas impatience economy and attention economy in mind. Then expressions concerningfreeness are looked for in the games' Google Play site texts. The modality and textual themes of these expressions are analysed. Then,these expressions are compared with the extent of freeness seen in the games. Gricean pragmatics and the synthesis of ‘free’ are used to determine whether the Google Play sites are co-operative with their descriptions. After this, it is speculated how the non-co-operative Google Play texts might cause misunderstandings. This is done by usingRelevance Theory and the theory of encoding and decoding. Out of ten games analysed, five were labelled as free, and each of the five had various restrictions in them. Reasons for this were speculated to be mostly commercial; the freeness had to be emphasised to make the product desirable. This, however, was thought to be possibly misleading for example because of the low degree of symmetry between the encoder and the decoder.